2000
DOI: 10.1118/1.1286554
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields with photon beams: Dose calculation using electron multiple‐scattering theory

Abstract: Strong transverse magnetic fields can produce large dose enhancements and reductions in localized regions of a patient under irradiation by a photon beam. We have developed a new equation of motion for the transport of charged particles in an arbitrary magnetic field, incorporating both energy loss and multiple scattering. Key to modeling the latter process is a new concept, that of "typical scattered particles." The formulas which we have arrived at are particularly applicable to the transport of, and deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The dose reduction is due to the loss of transient charged particle equilibrium downstream from the magnetic field. Jette [6,7] confirmed this effect by using electron multiple‐scattering theory and Monte Carlo calculations. Li et al [8] also demonstrated the effect along the central axis of the radiation beam using idealized step, ramp, and dipole fields.…”
Section: Introductionmentioning
confidence: 90%
“…The dose reduction is due to the loss of transient charged particle equilibrium downstream from the magnetic field. Jette [6,7] confirmed this effect by using electron multiple‐scattering theory and Monte Carlo calculations. Li et al [8] also demonstrated the effect along the central axis of the radiation beam using idealized step, ramp, and dipole fields.…”
Section: Introductionmentioning
confidence: 90%
“…14 -16 To keep up with the experimental work, Jette 17 has recently worked out the general equation of motion of a particle traveling in a material under the influence of a magnetic field. The continuous slowing down approximation and multiple scattering were included.…”
Section: Current and Future Workmentioning
confidence: 99%
“…Suppose a patient is irradiated by a photon beam in the presence of a magnetic field with a strong transverse component. From previous work [1][2][3] we know that, if the magnetic field has appropriate characteristics, its addition can create very large dose enhancements in localized regions, as well as large dose reductions distal to the enhanced-dose region. In Ref.…”
Section: Introductionmentioning
confidence: 99%